Cone‐beam computed tomography and the dentist. Issue 1 (14th July 2015) - MacDonald, David
Abstract: Although cone‐beam computed tomography (CBCT) is just 15 years old, it has revolutionized the practice of dentistry, so much so, there is hardly a dental specialty which has not been affected by this technology. Nevertheless, it presents the dentist with a number of important challenges. An initial steep learning curve must be addressed without unnecessary exposure to the patient. This is particularly important when the patient is a child.